Peran Penting Aspek-aspek Tata Kelola Perusahaan Dalam Meningkatkan Tingkat Pengungkapan Wajib Laporan Keuangan (Studi Pada Perusahaan Sektor Pertambangan Di Indonesia) - muhammmad yusuf akbar Alfatta; Sulardi Sulardi (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2019)
The influence of corporate governance aspects on mandatory disclosure financial report in Indonesia will be examined in this study to provide relevant information about it. The corporate governance aspects measured by number of commissioner member, independent commissioners proportion, president commissioner educational background, number of director member, independent directors proportion, and audit commitee member. All mining industry companies from 2014 to 2016 hich are listed on the Indonesia Stock Exchange (BEI) will be used on this study as population data. Secondary data obtained from financial reports and annual reports of 36 mining industry companies from 2014-2016. The results from multiple regression analysis in this study prove that the number of commissioner member and president commissioner educational background gives positive and significant effect to the mandatory disclosure level of financial statements of mining industry companies in Indonesia. This Results can be used by government agencies to evaluate the regulation of mandatory disclosure. In addition, the results from this study also can be used by companies to improve supervision related to corporate governance. Limitations in this study is the sample data used can not represent these results in other sectors companies.